INTERNAL CONTROL SYSTEM: A MANAGERIAL TOOL FOR PROPER ACCOUNTABILITY A CASE STUDY OF NIGERIA CUSTOMS SERVICE - Adewale, Odunayo Henry (European Scientific Journal, ESJ, 2014)
This study is examines the part played by internal control system in the management of Nigeria Customs Service. It recognizes two main groups of players in the Nigeria Customs Service namely, administration and enforcement from which 100 officers responded to a validated questionnaire titled ‘Nigeria Customs Service Participation Questionnaire’ (NCSPQ) which was validated and the reliability coefficient was found to be 0 . 71. Three research questions and three hypotheses were raised and tested in the study. Analysis of data reveals that significant difference existed between internal control system and proper accountability. Also, effective utilization of Information Technology plays important role in the collection of custom duties. The study also ascertains that effective internal control system ensures high revenue generation. However a positive correlation was found to exist between internal check and high level of accountability. These findings provide vivid evidence for recommendations such as adequate motivation of officers to avoid financial fraud; information technology gadgets should be provided for all commands and competent team, of experts to work out the logic of standard internal control should be put in place.